Broadcast Journalism of Private Radio in Cirebon, Indonesia, in the Convergence Era - Afiaty Fajriyah Ningrum; Justito Adiprasetio (Asian Journal of Media and Communication, 2021)
. Convergence is a deep integration of knowledge, tools, and all relevant areas of human activities. As an inevitable condition, convergence has also changed a lot of aspects of mass media at the international, national, and local levels. This study elaborates how the local radios in Cirebon, namely Sindangkasih FM, Suara Gratia FM, and Cirebon Radio, are adapting to the convergence culture. This study seeks to demonstrate how the convergence culture can affect private broadcast media, which are not in the epicentrum of media in Indonesia. This study indicates that these three private radios in Cirebon have tried to adapt to the convergence culture in minimally three aspects, namely structural, information coverage, and news presentation or storytelling convergence. The structural convergence happened at the organizational structure of the radio, in which more direct and fluid coordination in the newsgathering and writing processes is applied. At the news coverage level, reporters and scriptwriters are responsible for managing news content for old radio broadcasts and new online media as well. At the news presentation level, the news is not only broadcasted but also reported on new online channels, such as websites and social media. These convergences have further created a more convergent newsroom, including integrating journalism workflows, applying multiskilled journalism and resource sharing, using various technological tools, creating interactivity with the audience, and expanding the audience reach.Keywords: journalism, convergence, broadcasting, interactivity, radio